2019
DOI: 10.3390/heritage2020087
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and Surface Hardness Surveying of Stone Damaged by Ballistic Impact

Abstract: Recent instances of the destruction of cultural assets in conflict zones have demonstrated the need to develop methods which will allow for the assessment of damage to heritage stone in the field. In particular, non-destructive methods would be invaluable when working on sites damaged by contemporary ballistics. Permeability (TinyPerm 3) and surface hardness (Equotip) surveys of stone damaged by 7.62 × 39 mm (AK-47) projectiles were undertaken to determine the ability of these methods to identify the spatial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 25 publications
6
20
0
Order By: Relevance
“…Surface observations within the impact crater and spall zone show a shift of fracturing towards circumgranular pathways with increased distance from the impact, which is also seen throughout the subsurface sections and reflected in the fracture intensity plots. The micro-fractures provide evidence to support Gilbert et al's [7] suggestion that increased permeability and decreased surface hardness associated with the impact crater is related to micro-fracturing, as well as mirroring observations of grain fracture proximal to impact by Mol et al [42]. Gilbert et al [7] observed a light powdery appearance on the crater floor and a smaller surface hardness reduction relative to other areas of the impact damage.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Surface observations within the impact crater and spall zone show a shift of fracturing towards circumgranular pathways with increased distance from the impact, which is also seen throughout the subsurface sections and reflected in the fracture intensity plots. The micro-fractures provide evidence to support Gilbert et al's [7] suggestion that increased permeability and decreased surface hardness associated with the impact crater is related to micro-fracturing, as well as mirroring observations of grain fracture proximal to impact by Mol et al [42]. Gilbert et al [7] observed a light powdery appearance on the crater floor and a smaller surface hardness reduction relative to other areas of the impact damage.…”
Section: Discussionsupporting
confidence: 71%
“…This study extends the work of Gilbert et al [7] by characterising the surface morphology of impact damage and quantifying macro-scale fracture networks using 3D models generated by photogrammetry. It describes the microscale surface damage within the crater using electron microscopy and highlights the link to subsurface damage observed through thin section microscopy and fracture intensity analysis.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations